STRATEGI ORIENTASI PADA INDUSTRI MANUFAKTUR - Akbar Kurniawan; Muhammad Yasin (CV. Denasya Smart Publisher, 2024)
The purpose of this study is to determine the manufacturing industry strategy in accelerating economic growth in Indonesia. The Indonesian manufacturing industry has become a significant contributor to the country's economy, contributing more than 20% of GDP from 2005 to 2014. This contribution increased by 27.4% from 2005 to 2014, and 19% in 2018. This industry is the subject of research, especially in the Indonesian region, because the priority of this sector is high. The two main indicators of productivity are Total Factor Productivity (TFP) and Efficiency (EFI), which can be used as a reference for Indonesian manufacturing performance. To address consumer demand and meet unmet needs, companies must understand market potential and focus on market needs in product development. Focusing on the market will improve its performance, and the success of the company depends not only on product quality but also on marketing strategies and new innovations. The two most important components that contribute to economic growth through innovation are innovation and management that is oriented towards innovation and action to solve problems.